اتجاهات اعضاء هيئة التدريس نحو تقويم ادائهم : دراسة ميدانية على جامعة الزقازيق - ناصف، محمد أحمد حسين Nassef, Mohammed Ahmed Hussein; عتريس، محمد عيد (جامعة الزقازيق - كلية التربية, 2012)
هدفت الدراسة إلى التعرف على اتجاهات أعضاء هيئة التدريس نحو تقويم أدائهم، والاستفادة من ذلك في تطوير نظام تقويم أداء أعضاء هيئة التدريس. \ واستخدمت الدراسة المنهج الوصفي، كما قامت الدراسة بإجراء دراسة ميدانية على عينة ممثلة من أعضاء هيئة التدريس بالكليات النظرية والعملية بجامعة الزقازيق. \ وسارت الدراسة في الخطوات الآتية: \ -\ تقويم الأداء: المفهوم، الأهداف، المعايير، المبادئ، العوامل المؤثرة، والخطوات. \ -\ تقويم أداء أعضاء هيئة التدريس بالتعليم الجامعي \ أولاً: الأداء التدريسي. \ ثانياً: الأداء البحثي. \ ثالثاً: أداء خدمة المجتمع. \ -\ الدراسة الميدانية. \ -\ نتائج الدراسة ومقترحاتها في مجالات (أبعاد) الأداء الثلاثة: التدريس، البحث العلمي، وخدمة المجتمع. Faculty Members Attitudes Toward Evaluating Their Performance Field for the University of Zagazig \ The study aimed to identify the attitudes of faculty members toward evaluating their performance , and take advantage of this in the development of evaluating the faculty members system . \ The study used a descriptive approach, the study has also conducted a field study on a representative sample of faculty members of the theoretical and practical faculties in Zagazig University. \ The study proceeded in the following steps : \ -Evaluation of performance: (The concept, standards, .principles, factors, and steps). \ - Evaluation of the performance of faculty members in university education: \ First: Teaching performance. \ Second : Research performance . \ Third : The performance of community service. \ Field study. \ -Results of the study and their proposals in the fields (dimensions) performance trio: (Teaching, scientific research , community service) \ Key words (Attitudes - Faculty members _ Performance evaluation _ Teaching performance - research performance community service performance).
713158 789789
Keywords: هيئة التدريس -- اتجاهات اعضاء هيئة التدريس -- تقويم الاداء -- الاداء التدريسي -- جامعة الزقازيق -- مصر